All the reasons why: Exploring the relationship between morally controversial content in 13 Reasons Why and viewers' moral rumination - Daalmans, Serena; Kleemans, Mariska; Van Erp, Cedra; Weijers, Addy (Frontiers in Communication, 2022)
Controversial media content has mainly been dealt with in relation to concerns about how the media we consume might be detrimental to its viewers as individuals and society at large. Nevertheless, researchers have started to take a different approach to these types of content, namely that these might lead to processes of reflective appropriation, meaning-making, and moral rumination. Via qualitative in-depth interviews with young adults (N = 45, age 18-24), we sought to gain deeper insights into the experiences of and reflective thoughts (i.e., moral rumination) about controversial media content. To map when and what forms of moral rumination are incited in viewers, we chose a popular example of a morally conflicted and highly controversial type of media content, namely the Netflix series 13 Reasons Why. The results reveal that moral rumination can exist in at least two forms, morally conclusive (i.e., rumination that ends in a moral judgment) and morally inconclusive (i.e., rumination that does not formulate a moral judgment but remains morally in doubt) rumination. The grounds for the ruminations are mostly text-based or based on the interaction of text and viewer characteristics, and are mostly focused on the show's central themes, such as suicide, guilt and responsibility, sexually transgressive behaviors, and themes tied to identity formation. Overall, the tendency of morally complex entertainment to promote moral rumination suggests that such material should be examined as a type of eudaimonic entertainment, which argues that viewers reflect on how the meaning of the content relates to their own lives.